2003
DOI: 10.1016/s0002-9149(03)00897-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aspirin on inflammatory markers in patients after acute myocardial infarction

Abstract: The aim of this study was to assess the influence of aspirin on selected inflammatory markers in patients recovering from acute myocardial infarction (AMI). Patients participating in the Warfarin Aspirin Re-Infarction Study-II were randomized to either aspirin 160 mg/day or aspirin 75 mg/day + warfarin, or warfarin alone after AMI. After AMI, aspirin 160 mg/day was associated with significantly lower levels of high-sensitivity C-reactive protein and tumor necrosis factor-alpha than warfarin alone over 4 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 149 publications
(168 reference statements)
1
32
0
Order By: Relevance
“…Several previous studies demonstrated anti--inflammatory effect of low doses of ASA and clopidogrel, mainly in patients with CAD [18][19][20][21][22][23][24][25]. The results of subanalysis of Physician's Health Study suggested that cardioprotective effect of ASA correlated with its anti-inflammatory effect [26].…”
Section: Discussionmentioning
confidence: 96%
“…Several previous studies demonstrated anti--inflammatory effect of low doses of ASA and clopidogrel, mainly in patients with CAD [18][19][20][21][22][23][24][25]. The results of subanalysis of Physician's Health Study suggested that cardioprotective effect of ASA correlated with its anti-inflammatory effect [26].…”
Section: Discussionmentioning
confidence: 96%
“…Primary prevention with ASA is widely applied, however, not only because of its cardioprotective impact but also because there is increasing evidence of chemoprotection by ASA against cancer (96). Regarding its effect on the inflammatory response, the reduction of CRP levels by ASA has also been confirmed in other patient cohorts including subgroups with stable CAD (97) and ACS (98,99). Furthermore, ASA treatment reduces levels of IL-6, MCP-1, transforming growth factor-β (TGF-β), and TNF-α (97-100) but does not affect platelet-leukocyte interactions (101) (▶ Table 3).…”
Section: Platelets Inflammation and Antiinflammatory Drugs In Acs Anmentioning
confidence: 99%
“…associated with lower levels of inflammatory markers. [28] REFERENCES Strengths and limitations of study and is azurophilic granules of human neutrophils.…”
Section: Resultsmentioning
confidence: 99%